(untitled) (Indonesian Economic Justice Review, 2024)
This paper critically examines the impact of Indonesia’s economic policies on labor rights, with a focus on how policy decisions shape the working conditions and legal protections for laborers in various sectors. Despite substantial economic growth in recent decades, Indonesia’s labor market remains characterized by precarious work conditions, low wages, and a significant informal labor sector. The paper analyzes key policies such as the 2003 Manpower Law, the 2015 Omnibus Law, and the National Employment Policy, assessing how they address or exacerbate issues such as job security, workers’ rights to collective bargaining, and social protections. By reviewing government efforts to improve labor standards, such as the implementation of minimum wage policies and social security programs, the paper explores the limitations of these policies in tackling structural inequalities and ensuring fair labor practices. The study also investigates the role of trade unions, civil society, and international labor organizations in advocating for workers’ rights and influencing policy changes. The findings reveal that while there have been some improvements in labor conditions, Indonesia’s economic policies often prioritize economic growth and investment over labor rights, leading to the marginalization of vulnerable workers. The paper concludes by proposing recommendations for enhancing labor rights, including the strengthening of labor laws, better enforcement mechanisms, and more inclusive economic policies that prioritize workers’ well-being.